On Runge approximation and Lipschitz stability for a finite-dimensional Schrödinger inverse problem - Rüland, Angkana; Sincich, Eva (Arxiv, 2020)
In this note we reprove the Lipschitz stability for the inverse problem for the Schr\"odinger operator with finite-dimensional potentials by using quantitative Runge approximation results. This provides a quantification of the Schr\"odinger version of the argument from Kohn and Vogelius in Comm. Pure Appl. Math. (1985) and presents a slight variant of the strategy considered by Alessandrini, de Hoop, Gaburro and Sincich in Asymptotic Analysis (2018) which may prove useful also in the context of more general operators.